KEBIJAKAN MODEL PEMBELAJARAN MOTESSORI DALAM MENGENAL HURUF DI RA AL- IHSAN BANDUNG - Rida Nurfarida; Supiana; Qiqi Yuliati Zakiah (Tarbiya Islamica, 2021)
Policy Analysis Problems PP No. 27 of 1990 Chapter I article 1 paragraph 2 and RI Law number 20 of 2003 concerning the national education system article 28 in RA Al-Ihsan Bandung whether the policy is appropriate or not appropriate if applied in this educational institution. . The purpose of this study is to discuss the policy of the Montessori Learning model in recognizing letters at RA Al-Ihsan Bandung. The research method uses qualitative where the data is presented in a narrative manner rather than based on statistics. The research method uses a qualitative approach, collecting data through interviews, observations and documentation studies. The results show that the PP Policy No. 27 of 1990 Chapter I Article 1 paragraph 2 and Law No. 20 of 2003 concerning the National Education System Article 28 are in accordance with policy at RA Al-Ihsan Bandung because the Montessori Learning model in recognizing letters is appropriate and has a good impact. Until it can be implemented and implemented.